Our Gospel (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The present work consists of the play Nosso Evangelho with the introduction of the author Edson Sodré, founder of the Kriadaki Group Theater and student of the Teaching of Theater at Unirio. He is still serving time in the semi-open regime. The play seeks a simple way of communicating, composed of acid and ironic criticisms to the diferente layers of society, including the theater itself. There are several references to different dramaturgical writers and thinkers in order to attract the eyes of people from the poorest sections of society.
Keywords: Theater; Education; Culture; Prison